Evolución en la generación internacional de actividades tecnológicas: Un análisis a nivel de áreas tecnológicas - M. A. Quintás Corredoira; J. M. García Vázquez (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2006)
In the last years, there has been detected an increasing internationalisation of the technological activities. This paper studies the international generation of technologies, which is the way of internationalising the technological activities that presents a weaker empirical and controversial support. So, we study, making a distinction of six technological areas, the level of international generation of technological activity that present the multinationals, the home country of the multinationals most internationalised and the countries where their international patents have been generated. To carry out this work we construct a database that gathers the patents applied by the European route, between the year 1978 and 2000, from 1.663 multinationals with activity in Spain and from their 62.928 subsidiaries distributed all over the world.
Keywords: 330; international generation of technology; patents European route; multinationals